Role of platelets in chronic liver disease and acute liver injury. Issue 2 (27th August 2013) - Nowatari, Takeshi; Murata, Soichiro; Fukunaga, Kiyoshi; Ohkohchi, Nobuhiro
<x xml:space="preserve">Abstract</x> Platelets contain not only hemostatic factors but also many growth factors that play important roles in wound healing and tissue repair. Platelets have already been used for the promotion of tissue regeneration in the clinical setting, such as dental implantation and plastic surgery. Thrombocytopenia, which is frequently found in patients with chronic liver disease and cirrhosis, is due to various causes such as decreased thrombopoietin production and accelerated platelet destruction caused by hypersplenism. However, the relationship between thrombocytopenia and hepatic pathogenesis and the role of platelets in chronic liver disease are poorly understood. In acute liver injury, it is reported that platelets are recruited to the liver and contribute to liver damage by promoting the induction of chemotactic factors and the accumulation of leukocytes in the liver, whereas platelets or mediators released by platelets can have a protective effect against liver injury. In this review, we highlight the recent accumulated knowledge concerning the role of platelets in chronic liver disease and acute liver injury.